Adenoviral based gene therapy for cancer in human and animals: a review - Tan, Seok Shin; Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi (Universiti Putra Malaysia Press, 2011)
Adenovirus vector is the most common used vector in clinical gene therapy. The development of adenovirus from the first generation until the helper-dependent adenovirus vector has greatly reduced toxicity and immunogenicity. The helper-dependent adenovirus can also prolong transgene expression. Tissue- or disease-specific approach has been used to improve the specificity of adenoviral vector for cancer gene therapy. This review summarizes some adenoviral gene therapy and targeting approaches available for human cancer as well as animal cancer.